Barking up the wrong tree : the surprising science behind why everything you know about success is (mostly) wrong - Barker, Eric (New York, NY HarperOne, an imprint of HarperCollinsPublishers, 2017)
Discusses the components of success and how to achieve it, discussing such topics as work-life balance, grit, cooperation, confidence, and personality weaknesses.
Introduction. What really produces success? -- Should we play it safe and do what we're told if we want to succeed? -- Do nice guys finish last? -- Do quitters never win and winners never quit? -- It's not what you know, it's who you know (unless it really is what you know) -- Believe in yourself...sometimes -- Work, work, work...or work-life balance? -- What makes a successful life?
Includes bibliographical references (pages 269-307).
104975
Keywords: Success -- Psychological aspects; Success -- Social aspects